2008
DOI: 10.1017/s1478061508925470
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-free electrolytes and calcium supplementation in an endurance race

Abstract: Some of the clinical signs seen in horses during endurance races may result from increases in neuromuscular excitability and are related to plasma [K þ ] and [Ca þ þ ]. The present study aimed to test the following hypotheses:(1) Potassium supplementation will affect plasma [K þ ] and may result in clinical signs related to neuromuscular hyperexcitability during an 80 km endurance ride.(2) Plasma [Ca þ þ ] will reflect dietary cation-anion balance (DCAB) and calcium intake. Feeding with a high DCAB and high di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
0
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
3
0
0
1
Order By: Relevance
“…Electrolyte mixtures intended to replete sweat losses contain abundant potassium (Flaminio and Rush 1998), which may be contraindicated for higher speeds. This proposition has been supported by studies of endurance races (Hess et al 2003(Hess et al , 2005 and is further tested in the present study on the treadmill.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Electrolyte mixtures intended to replete sweat losses contain abundant potassium (Flaminio and Rush 1998), which may be contraindicated for higher speeds. This proposition has been supported by studies of endurance races (Hess et al 2003(Hess et al , 2005 and is further tested in the present study on the treadmill.…”
Section: Introductionsupporting
confidence: 77%
“…Data from a previous review indicated that plasma [K+] increases in speeds of 4 misec on flat races and, therefore, K should not be added to the electrolyte formulas during exercise (Kronfeld 200 1 ). In previous studies (Hess et al 2003(Hess et al , 2005 K supplementation also yielded higher plasma [K+]. Plasma [K+] are comparable to levels found during repeated sprints in Arabian horses (Taylor et al 1995), but lower than Thoroughbred horses during high intensity exercise (Harris and Snow 1992).…”
Section: Ions Related To Excitabilitysupporting
confidence: 55%
See 1 more Smart Citation
“…Robert et al (2010) presented a reference for plasma sodium concentration among 130 and 147 mmol/l which is close to that observed in this study. Schott II et al (2002) observed a sodium concentration of 138 mmol/l in horses before exercise, while Nyman et al (1996) and Hess et al (2008) observed values of 136 141 mmol/l, respectively. Robert et al (2010) defined a reference range of plasma chloride concentration from 92 to 100 mmol/l.…”
Section: Blood Variablesmentioning
confidence: 95%
“…Medžiagų apykaitos pasikeitimai per ištvermės rungtis siejasi su organizmo dehidratacija, elektro litų ir kraujo dujų parametrų pasikeitimu, stipriu prakaitavimu (Foreman et al, 1996;Hess et al, 2008;Fieldieng, 2009;Trigo, 2010;Lawrie, 2012). Vieni iš startavusių žirgų baigia distanciją, kiti yra diskvalifikuojami dėl medžiagų apykaitos sutri kimų, miopatijų, širdies ir kraujagyslių sistemos miopatijos arba sutrikimų, atsiradusio šlubavimo, pasireiškusių dieglių (Fielding, Dechant, 2012) ar kitų priežasčių (Schott et al, 2006;Hess et al, 2008;Fielding et al, 2009;Alexander, Haines, 2012). Todėl labai svarbu kontroliuoti visus fizio loginius organizmo procesus, vystyti geras orga nizmo adaptacines funkcijas ir tinkamai paruošti žirgą fiziniam krūviui (Whiting, 2009).…”
Section: įVadasunclassified